OPERATIONAL PERFORMANCE OF A TRANSFUSIONAL AGENCY: EVIDENCE OF A PUBLIC HEALTH CARE INSTITUTION FROM THE NORTHEAST OF BRAZIL - Callado, Fabia Michelle Rodrigues de Araújo; Callado, Antônio André Cunha; Lima, Andréa Maria de (Management Control Review, 2016)
The increase of the populations, expansion of human longevity, changes in the epidemiology of societies and the importance of technological advances resulting from greater understanding of the physiology, pathology and the health care treatments in most medical areas have broadened the possibilities of increasingly complex procedures with consequently greater demand for blood and transfusional agencies play a relevant role in it. Providing blood products for medical care procedures has become a major concern among health care institutions and the improvement of performance of transfusional agency is a relevant current issue. This paper aims to analyze the operational performance of a public transfusional agency of a public health care institution from the northeast of Brazil. Data regarding medical procedures, demand for blood, blood supply, and blood use from January to November of 2014 were gathered. Descriptive statistics was used to set up a database and hypothesis tests were used to analyze the significance of operational improvement from the managerial practices implemented. The results present high rates of operational efficiency. The results also indicate the managerial practices have improved the efficiency. In addition, results indicate that the metrics used were able to assist the decision making process of blood supply from the transfusional agency in this public health care institution. Contribute to the improvement of managerial practices regarding transfusional agency from the perspective of performance measurement. Further studies may amplify the understanding of this relevant health care issue.